On the Geometry of the Movements of Particles in a Hamilton Space - A. Ceylan Coken; Ismet Ayhan (Abstract and Applied Analysis)
We studied on the differential geometry of the Hamilton space including trajectories of the motion of particles exposed to gravitational fields and the cotangent bundle.